MHD slip flow past an extending surface with third type boundary condition and thermal radiation effects - Gururaj, David Maxim Anthony; Sundaram, Dhanasekar; Parthiban, V. (Zielona Góra: Uniwersytet Zielonogórski)
MHD slip flow past an extending surface with third type (convective) boundary condition and thermal radiation is analysed. The governing momentum and energy equations are converted into set of nonlinear ordinary differential equations using appropriate similarity transformations. The Fourth-Order Runge-Kutta shooting method is applied for obtaining the numerical solution of the resulting nonlinear ordinary differential equations.
Keywords: third type (convective) boundary condition; slip flow; thermal radiation; extending surface